Strategi Customer Relationship Management (CRM) PT Global Surya Medika Dalam Mempertahankan Loyalitas Pelanggan - Regita Cahya Ramadhanti; Tira Fitriawardhani; Julyanto Ekantoro (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to examine the CRM (Customer Relationship Management) strategies applied by the Customer Retention Unit of PT Global Surya Medika Surabaya to achieve customer loyalty. The research is based on the concepts of Financial Benefit, Social Benefit, and Structural Tie as proposed by Kotler and Keller. This study uses a case study approach with qualitative methods through interviews, observations, and literature review. The results of this study show how PT Global Surya Medika implements CRM to retain customers. Financial Benefit, Social Benefit, and Structural Tie are forms of CRM implementation at PT Global Surya Medika in maintaining customer relationships by combining the communication capabilities of Public Relations and Marketing with technology. It starts with identifying customers through Repeat Purchase, Rejecting Competitors, and Word of Mouth. The types of customer loyalty obtained by PT Global Surya Medika are weak loyalty and premium loyalty. Premium loyalty is a very high level of customer loyalty, where customers are not only loyal but become enthusiastic fans who are hard to tempt by competitors and are even willing to pay more. Weak loyalty is a superficial level of loyalty, where customers keep purchasing not out of brand love but due to convenience, lower price, or availability. The company then differentiates customers based on existing customer data, interacts through various intermediary platforms and direct communication, and continuously modifies health equipment service offerings and updates medical devices within a certain time frame according to health procedures to match customer needs.